2000
DOI: 10.1159/000016782
|View full text |Cite
|
Sign up to set email alerts
|

Chaperones in the Parotid Gland: Localization of Heat Shock Proteins in Human Adult Salivary Glands

Abstract: Heat shock proteins (HSPs) are expressed or increased in response to various biological stresses. Moreover, these ‘stress proteins’ seem to be expressed by some cells living in physiological conditions. From then on, they could play an important physiological role in normal cell functioning. The best-known physiological role of these HSP proteins is to act as ‘molecular chaperones’. In this context, we have investigated the immunohistochemical expression of HSP27, HSP70, HSP90 and HSP110 in 10 human adult sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…albumin, blood group antigens, etc.). A passive transport or a small-capacity active transport [26,27] from the striated duct cells of human salivary glands is also possible, since a higher amount of Hsp70 was detected in these cells compared with others with immunocytochemical methods [82].…”
Section: The Origin Of Salivary Chaperone Hsp70mentioning
confidence: 99%
“…albumin, blood group antigens, etc.). A passive transport or a small-capacity active transport [26,27] from the striated duct cells of human salivary glands is also possible, since a higher amount of Hsp70 was detected in these cells compared with others with immunocytochemical methods [82].…”
Section: The Origin Of Salivary Chaperone Hsp70mentioning
confidence: 99%
“…Although the localization of iNOS and the HSPss and their roles in normal salivary gland are well documented [1,5,10,21,31], little information is available on their role in neoplasm of salivary gland [4,5]. The present study showed iNOS and the HSPs are widely localized at neoplastic epithelium in pleomorphic adenoma.…”
Section: Discussionmentioning
confidence: 45%
“…The sections were rinsed in PBS and incubated with streptavidin-biotin peroxidase complex (SAB-PO kit; Histofine, Nichirei, Tokyo, Japan) according to manufacturer procedure, reacted with 3,3'-diaminobenzidine (DAB) and hydrogen peroxide for 5 min at room temperature, rinsed in distilled water, dehydrated, and mounted in Malinol. As a positive control, the staining in the normal salivary glands adjacent to the tumors was used with reference to previous reports [5,31]. All individuals were informed about the purpose of the study and consented to the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research is required to identify the influence of the autonomic nervous system on eHSP70 secretion. Vanmuylder et al (2000) reported that eHSP70 is strongly expressed in epithelial cells of the striated ducts and weakly expressed in the acinar cells of the salivary glands. Therefore, it can be inferred that constitutive salivary eHSP70 is secreted from the ductal cells.…”
Section: Discussionmentioning
confidence: 99%